Fighting antibiotic resistance—strategies and (pre)clinical developments to find new antibacterials. (19th December 2022) - Walesch, Sebastian; Birkelbach, Joy; Jézéquel, Gwenaëlle; Haeckl, F P Jake; Hegemann, Julian D; Hesterkamp, Thomas; Hirsch, Anna K H; Hammann, Peter; Müller, Rolf
Abstract: Antibacterial resistance is one of the greatest threats to human health. The development of new therapeutics against bacterial pathogens has slowed drastically since the approvals of the first antibiotics in the early and mid‐20 th century. Most of the currently investigated drug leads are modifications of approved antibacterials, many of which are derived from natural products. In this review, we highlight the challenges, advancements and current standing of the clinical and preclinical antibacterial research pipeline. Additionally, we present novel strategies for rejuvenating the discovery process and advocate for renewed and enthusiastic investment in the antibacterial discovery pipeline. Abstract : Antibacterial resistance is one of the greatest threats to human health. This review highlights the challenges, advancements and current standing of the clinical and preclinical antibacterial research pipeline.